ORAL CORRECTIVE FEEDBACK AND LEARNER UPTAKE IN A YOUNG LEARNER EFL CLASSROOM A CASE STUDY IN AN ENGLISH COURSE IN BANDUNG - Maolida, Elis Homsini (2013)
This study reports various types of oral corrective feedback in relation to learner uptake in an English class for young learners. It unfolds types of teacher's oral corrective feedback and their distribution in classroom interaction and learner uptake following the different types of oral feedback. This study employed a qualitative research design, embracing the characteristics of a case study. The data were collected by means of approximately 9 hours audio and video recording to capture types of teacher's oral corrective feedback and learner uptake in the classroom interaction which were then transcribed and coded by using the categorization from Lyster&Ranta (1997) and Ellis (2009). The data were also obtained from stimulated recall interview one week after the observation finished. The first finding reveals that the teacher employed seven types of oral corrective feedback: recast, elicitation, clarification request, explicit correction, repetition, metalinguistic feedback, and paralinguistic signal. In this case, the teacher's choice to give oral corrective feedback was led by three motives: the teacher's perception of the benefit of correction for language learning, the teacher's professional concern, and the teacher's intention to avoid fossilization. It is also revealed that in employing different types of oral corrective feedback, the teacher put several aspects into her consideration such as learners' proficiency, learners' types of spoken error, and learning objectives. The distribution of oral corrective feedback in the interaction shows that recast was the most preferred strategy even though it resulted in the least frequency of learners' uptake. The second finding reveals that the learners responded to the teacher's oral corrective feedback with uptake or topic continuation. The learner uptake in the form of self-repair, peer-repair, repetition and incorporation were identified as repair while the learner uptake in the form of same error, different error, partial error, hesitation and acknowledgement were identified as need-repair. The distribution of learner uptake following different types of oral corrective feedback shows that elicitation, clarification request, repetition, metalinguistic feedback and paralinguistic signal repair resulted in a higher number of learner uptake comparing to recast and explicit correction. It is also noteworthy that elicitation and repetition led to the highest number of repair. The results imply that the types of oral corrective feedback utilized by the teacher influence the types of learner uptake. In this case, output prompting feedback strategies are more successful in encouraging learner uptake and learner generated repair than input providing feedback strategies. Keywords: Oral corrective feedback, learner uptake, young learner